Meningkatkan Kepercataan Diri Anak Panti Asuhan Cinta Kasih Menggunakan Teknik Behavior Modification - Sadiah Muayyadah; Hairani Siregar (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Every child has different aspects of abilities. Characteristics of children's ability must be trained in accordance with their developmental stage. Confidence is one of the aspects that needs to be promoted to enhance children's social ability. Confidence is believing that one has the best ability to suffice, realize, and use it to solve the problems in the best situation. Confidence isn't formed by itself, but it's related to one's personality and influenced by experiences from an early age. The purpose of increasing confidence is so that children have the ability to believe in themselves to face the next stage of life. In this case, the purpose of this journal is to apply Behavior Modification Technique as a strategy to increase children's confidence, especially in Cinta Kasih Orphanage, Medan who needed help to increase their self-confidence. The process of providing assistance is interspersed with increasing their sense of community. Behavior Modification is an effort, a process, or an action to change behavior using the application of learning principles. Steps or procedures of Behavior Modification are: a. Identifying or describing target behavior, b. Identifying the cause of current behavior, c. Helping to choose the right solution, and d. Evaluating the results of Behavior Modification application.